Relevance of Frequency-Domain Analyses to Relate Shoe Cushioning, Ground Impact Forces and Running Injury Risk: A Secondary Analysis of a Randomized Trial With 800+ Recreational Runners - Malisoux, Laurent; Gette, Paul; Backes, Anne; Delattre, Nicolas; Cabri, Jan; Theisen, Daniel (Frontiers in Sports and Active Living, 2021)
The use of cushioning systems in running shoes is based on the assumptions that ground impact forces relate to injury risk and that cushioning materials reduce these impact forces. In our recent randomized trial, the shoe version with more cushioning (i.e. Soft shoe) was associated with lower injury risk. However, vertical impact peak force was higher in participants with the Soft shoe version. The primary objective of this study was to investigate the effect of shoe cushioning on the time, magnitude and frequency characteristics of peak forces using frequency-domain analysis by comparing the two study groups from our recent trial (i.e. Hard and Soft shoe group, respectively). The secondary objective was to investigate if force characteristics are prospectively associated with the risk of running-related injury. This is a secondary analysis of a double-blinded randomized trial on shoe cushioning with a biomechanical running analysis at baseline and a 6-month follow-up on running exposure and injury. Participants (n=848) were tested on an instrumented treadmill at their preferred running speed in the randomly allocated shoe conditions. The vertical ground reaction force signal for each stance phase was decomposed into the frequency domain using the discrete Fourier transform. Both components were recomposed into the time domain using the inverse Fourier transform. An analysis of variance was used to compare force characteristics between the two study groups. Cox regression analysis was used to investigate the association between force characteristics and injury risk. Participants using the Soft shoes displayed lower impact force (p<0.001, d=0.23), longer time to peak (p<0.001, d=0.25), and lower average loading rate (p<0.001, d=0.18) of the high frequency signal compared to those using the Hard shoes. Participants with low average and instantaneous loading rate had lower injury risk (Subhazard rate ratio (SHR) =0.49 and 0.55; 95% confidence Interval (CI) =0.25-0.97 and 0.30-0.99, respectively), and those with early occurrence of impact peak had greater injury risk (SHR=1.60; 95% CI=1.05-2.53). Our findings may explain the protective effect of the Soft shoe version previously observed. The present study also demonstrates that frequency-domain analysis may provide clinically relevant impact force characteristics. Trial registration number: NCT03115437 (11/04/2017, https://clinicaltrials.gov/).